2014
DOI: 10.4103/0970-0358.146611
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of negative pressure wound therapy on chemotherapeutic extravasation ulcers: An experimental study

Abstract: Context:The extravasation of the chemotherapeutic agents is not an unusual phenomenon. Necrosis of the skin and underlying structures has been reported, depending on the cytotoxicity of the extravasating drug. Despite the presence of some antidotes, such wounds tend to enlarge with time and are likely to resist the treatment.Aims:The objective of this study was to investigate the efficacy of negative pressure wound therapy (NPWT) on extravasation ulcers.Settings and Design:Animals were separated into two group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The application of negative pressure was found to prevent ulcer formation (8). These findings could not be confirmed by Isci et al (9), who investigated the efficacy of NPWT on established chemotherapeutic extravasation ulcers in albino rabbits. Their study revealed no significant difference in terms of inflammatory cell count, neovascularization, and granulation tissue formation between NPWT and conventional dressing groups (9).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The application of negative pressure was found to prevent ulcer formation (8). These findings could not be confirmed by Isci et al (9), who investigated the efficacy of NPWT on established chemotherapeutic extravasation ulcers in albino rabbits. Their study revealed no significant difference in terms of inflammatory cell count, neovascularization, and granulation tissue formation between NPWT and conventional dressing groups (9).…”
Section: Discussionmentioning
confidence: 71%
“…These findings could not be confirmed by Isci et al (9), who investigated the efficacy of NPWT on established chemotherapeutic extravasation ulcers in albino rabbits. Their study revealed no significant difference in terms of inflammatory cell count, neovascularization, and granulation tissue formation between NPWT and conventional dressing groups (9). NPWT, combined with limb salvage, has successfully been used as a bridge to delayed skin grafting in a patient with an extensive arm ulcer due to doxorubicin extravasation.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…At the cellular level, NPWT facilitates collagen synthesis, angiogenesis, and formation of granulation tissues. [ 15 17 ] Moreover, conventional wound dressing changes must be frequently undertaken, whereas NPWT requires a dressing change every 48 to 72 hours, thus reducing clinical staff workload. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%